Diseño del sistema virtual y la red de distribución de gas natural en el municipio de bucarasica desde el campo Cerro Gordo (2019)
This degree work explores the use of virtual gas pipeline technology for the transport of compressed natural gas (CNG). Where the virtual system was designed from the Cerro Gordo Field, towards the municipality of Bucarasica, accompanied by the design of the home natural gas distribution network in the municipal seat. Developed from the generalities of the producing field as a mother station and the municipality as a consumption center, where its demand was established to estimate the required monthly gas flow rate of 4200 m^3